2004
DOI: 10.1002/elps.200305703
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrochromatographic analysis of barbiturates in serum

Abstract: A capillary electrochromatographic method was developed for the separation of barbiturates. The separation was optimized in a 75 microm ID capillary, packed with 3-(1,8-naphthalimido)propyl-modified silyl silica gel (NAIP), studying the effect of buffer pH, buffer concentration, and mobile phase composition. Using an applied voltage of 20 kV and the short-end injection method (9 cm capillary effective length), the mobile phase of 1.0 mM citrate buffer (pH 5.0) containing 40% methanol provided the baseline sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…In the literature, different techniques, such as LC, GC and CE, have been used for the determination of barbiturate drugs in biological samples, [14][15][16][17][18][19][20][21][22]26,27 as summarized in Table 2. In these papers, samples such as urine, 14,16,19,21,26,27 plasma, 15 serum, 22 meat 17,18 and meconium 20 were analysed.…”
Section: Urine Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, different techniques, such as LC, GC and CE, have been used for the determination of barbiturate drugs in biological samples, [14][15][16][17][18][19][20][21][22]26,27 as summarized in Table 2. In these papers, samples such as urine, 14,16,19,21,26,27 plasma, 15 serum, 22 meat 17,18 and meconium 20 were analysed.…”
Section: Urine Samplesmentioning
confidence: 99%
“…In these papers, samples such as urine, 14,16,19,21,26,27 plasma, 15 serum, 22 meat 17,18 and meconium 20 were analysed. As can be observed from the table, the LODs obtained in our study are generally lower than those reported in other papers that focused on the determination of barbiturate drugs in urine samples by CE, except for the case of Kadi et al 26 and Botello et al 27 who reported similar LODs.…”
Section: Urine Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the 100 mM level the recovery of the drugs from human urine samples was better than 82%. A naphthyl-modified silica stationary phase (5 mm particles) was used by Ohyama et al [62] for the CEC separation of barbiturates. The structure of the stationary phase was similar to that prepared by the same group, shown in Fig.…”
Section: Pharmaceuticals In Biofluidsmentioning
confidence: 99%
“…The modification ratio of 3-aminopropyl siliyl silica gel with 4-sulfo-1,8-naphthalic anhydride was 0.523 mmol/g which was estimated from the percentage of carbon by elemental analysis. CEC columns packed with SNAIP were prepared by a slurry-packing technique as reported previously [28,29]. All columns were 37 cm long with a packed length of 9 cm.…”
Section: Stationary Phase and Column Preparationmentioning
confidence: 99%